2022
DOI: 10.1590/1807-1929/agriambi.v26n1p51-58
|View full text |Cite
|
Sign up to set email alerts
|

Production and post-harvest quality of mini-watermelon crop under irrigation management strategies and potassium fertilization

Abstract: The occurrence of water sources with a high concentration of salts stands out as a limiting factor for production in Northeast Brazil. Thus, the search for strategies that minimize the effect of salt stress on crops is of fundamental importance. In this context, this study was conducted with the objective of evaluating the production and post-harvest quality of Sugar Baby mini-watermelon fruits under different irrigation management strategies with saline water and potassium fertilization. The experiment was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…2016; Silva et al, 2022). However, these effects depend on the crop's development stage, duration of exposure to stress, type of salt present in the environment, and environmental, cultural, and irrigation management conditions (Lima et al, 2021;Silva et al, 2022;Wu et al, 2022). Therefore, strategies to mitigate salt stress and improve water use efficiency are essential.…”
Section: Etc Eto Kcmentioning
confidence: 99%
“…2016; Silva et al, 2022). However, these effects depend on the crop's development stage, duration of exposure to stress, type of salt present in the environment, and environmental, cultural, and irrigation management conditions (Lima et al, 2021;Silva et al, 2022;Wu et al, 2022). Therefore, strategies to mitigate salt stress and improve water use efficiency are essential.…”
Section: Etc Eto Kcmentioning
confidence: 99%
“…It was expected that the application of K2O, especially the highest dose, would result in watermelon fruit quality, since this element is strongly associated with fruit quality (SILVA et al, 2022). Lima Neto et al (2010) emphasize that environmental factors, in addition to genetic factors and the degree of maturation at the time of harvest, considerably influence the quality of watermelon fruits.…”
Section: Watermelon Fruit Quality Componentsmentioning
confidence: 99%
“…Lima et al [ 17 ] found that salt stress in the vegetative, flowering, and fruiting stages is a promising strategy for sesame cultivation in the semi-arid region of Brazil. Silva et al [ 18 ], in a study evaluating the production and post-harvest quality of mini-watermelon fruits, saline water irrigation management strategies, and potassium fertilization, concluded that irrigation with water of 4.0 dS m −1 in the flowering and fruit maturation stages is a promising strategy for cultivation, since it does not compromise the production, and fertilization with 50% of the K 2 O recommendation can be used in the cultivation of mini-watermelon without losses in production.…”
Section: Introductionmentioning
confidence: 99%